Epistemologi, Intelektual, dan Problem Dikotomi Keilmuan Pesantren (Studi Kasus di Pondok Pesantren As-Safi’i Desa Nogosari, Kecamatan Rambipuji, Kabupaten Jember): Epistemology, Intellectual, and the Problem of Knowledge Dichotomy in Islamic Boarding Schools (Case Study at As-Safi’i Islamic Boarding School, Nogosari Village, Rambipuji District, Jember Regency) - Hafidz Hafidz (Fenomena, 2015)
This study begins by developing a paradigm for managing Islamic boarding schools (pesantren) toward systematic, continuous, dynamic, and comprehensive educational thinking and direction. Systematic means that the educational direction is structured in stages of achievement, organized within a well-planned framework and evaluation monitoring. Continuous means that the educational direction is integrated with various evolving sciences without limiting itself to individualistic religious knowledge but also encompassing socially oriented religious knowledge. Dynamic means that the educational direction is more inclusive, open, and constantly evolving, not confined to a single school of thought but capable of exploring and developing existing schools of thought, as it is not an absolute, uncriticizable science. Comprehensive means that the educational direction is further developed in discussing the progress of knowledge, as the source of knowledge is one, namely the Qur’an and the Sunnah of the Prophet, which are then categorized into various disciplines for ease of discussion, and there is no concept of halal or haram in knowledge, as all knowledge ultimately leads to the glorification of the Creator, Allah Swt. Penelitian ini dimulai dengan mengembangkan paradigma pengelolaan pesantren menuju pemikiran dan arah pendidikan yang sistematis, berkesinambungan, dinamis, dan komprehensif. Sistematis artinya arah pendidikan lebih disusun dalam tahapan-tahapan pencapaian yang tersusun dalam satu perencanaan dan monitoring evaluasi yang baik. Berkesinambungan artinya, arah pendidikan dipadukan dengan berbagai perkembangan keilmuan yang terus berkembang tanpa membatasi diri pada satu keilmuan agama yang sifatnya individualistik, namun juga pada keilmuan agama yang sifatnya sosial. Dinamis artinya, arah pendidikan lebih inklusif, terbuka, dan terus bergerak, tidak terjebak pada satu pemikiran mazhab saja, namun dapat menclaah dan mengembangkan pemikiran mazhab yang sudah ada sebab ia bukanlah ilmu harga mati yang tidak dapat dikritik. Komprehensif artinya arah pendidikan lebih dikembangkan pada pembahasan perkembangan ilmu sebab pada dasarnya sumber ilmu itu satu, yakni al-Qur’an dan Sunnah Rasul, yang kemudian untuk memudahkan pembahasan dikelompokkan dalam berbagai disiplin ilmu tersendiri dan tidak ada halal dan haram dalam ilmu sebab pada dasarnya semua ilmu muaranya menuju pada pengagungan sang Khalik, Allah Swt.